(untitled) (Journal of Science and Technology, 2016)
The operations of the Wood Processing Industry (WPI) are generally associated with high levels of occupational hazards with consequent health risks. The purpose of this study was to assess the perceived occupational health hazards exposure and the effectiveness of the policies put in place to ensure the health and safety of workers in 14 randomly selected WPIs located at Ahensan, Asokwa and Kaasi industrial area in Kumasi. Primary data on occupational hazards and policies were obtained from the WPIs through observation, semi-structured interviews, individually administered questionnaires while secondary data on industrial accidents was obtained from Kumasi Metropolitan Labour Department (KMLD) and Department of Factories Inspectorate (DFI) for Ghana for the analysis. The study found the trend in perception of unsafe working environment increasing with decreasing size of companies. The WPI surveyed revealed vulnerability of the workers to occupational hazards and accidents as a result of inadequate engineering and administrative controls, and the low use of personal protective equipment. The lack of commitment by management to implement OSH policy where it existed, consideration of payment of insurance premium as sufficient protection for their workers, restrictive inspections, education and enforcement by under resourced DFI (which shows extent of government commitment to OSH) and Timber and Wood Workers union inability to project OSH agenda have contributed substantially to WPI’s neglect of workers health and safety. It appeared that statistics at the Labour Departments in Ghana will make a better case for OSH than the under estimated DFI figures which have been used extensively and consistently in the past, because workmen’s compensation provides an incentive for higher notification of industrial accident at the Labour Department.